Analysis of postmarket complaints database for the iFuse SI Joint Fusion System®: a minimally invasive treatment for degenerative sacroiliitis and sacroiliac joint disruption - Miller LE (Dove Medical Press, 2013)
Larry E Miller,1,2 W Carlton Reckling,3 Jon E Block21Miller Scientific Consulting Inc, Arden, NC, 2The Jon Block Group, San Francisco, CA, 3SI-BONE Inc, San Jose, CA, USABackground: The sacroiliac joint is a common but under-recognized source of low back and gluteal pain. Patients with degenerative sacroiliitis or sacroiliac joint disruption resistant to nonsurgical treatments may undergo open surgery with sacroiliac joint arthrodesis, although outcomes are mixed and risks are significant. Minimally invasive sacroiliac joint arthrodesis was developed to minimize the risk of iatrogenic injury and to improve patient outcomes compared with open surgery.Methods: Between April 2009 and January 2013, 5319 patients were treated with the iFuse SI Joint Fusion System® for conditions including sacroiliac joint disruption and degenerative sacroiliitis. A database was prospectively developed to record all complaints reported to the manufacturer in patients treated with the iFuse device. Complaints were collected through spontaneous reporting mechanisms in support of ongoing mandatory postmarket surveillance efforts.Results: Complaints were reported in 204 (3.8%) patients treated with the iFuse system. Pain was the most commonly reported clinical complaint (n = 119, 2.2%), with nerve impingement (n = 48, 0.9%) and recurrent sacroiliac joint pain (n = 43, 0.8%) most frequently cited. All other clinical complaints were rare (≤0.2%). Ninety-six revision surgeries were performed in 94 (1.8%) patients at a median follow-up of four (range 0–30) months. Revisions were typically performed in the early postoperative period for treatment of a symptomatic malpositioned implant (n = 46, 0.9%) or to correct an improperly sized implant in an asymptomatic patient (n = 10, 0.2%). Revisions in the late postoperative period were performed to treat symptom recurrence (n = 34, 0.6%) or for continued pain of undetermined etiology (n = 6, 0.1%).Conclusion: Analysis of a postmarket product complaints database demonstrates an overall low risk of complaints with the iFuse SI Joint Fusion System in patients with degenerative sacroiliitis or sacroiliac joint disruption.Keywords: arthrodesis, iFuse, lumbar, minimally invasive, sacroiliac